El efecto de biol más microorganismos eficientes (em) sobre el comportamiento agronómico del maíz (zea mayz l.) - León Macias, Erwin Manuel (2015)
The objective es of the research was to measure the effect of biol more effective microorganisms (EM) on the agronomic performance of maize (Zea mays L). The following hypothesis was formulated: The application of biol more efficient microorganisms EM preparation craft down in maize (Zea mays L.) at different doses increases your productivity. Complete randomized blocks with four treatments and 4 replications. Tukey test was performed at 5%. As for the days in regard to plant height at 30, 60 and 110 significant difference between treatments was found. To the shelf height cob significant difference was found between treatment being the T4 (1.5 L / 20l + EM) meeting with an average height of 1.67; the leaf area did not detect statistical significance and according to Tukey all treatments originated averages statistically equal to each other; variable percentage in the incidence of disease and insect damage, no statistical significance was detected and all treatments according Tukey averages originated statistically equal, flowering day detected by Tukey statistical significance and all treatments originated statistically averages equal to each other; maturation rate detected by Tukey statistical significance and all treatments averages originated statistically equal, in the number of ears per plant was detected by Tukey statistical significance and all treatments originated statistically averages equal to each other; in the number of ears per row, weighing 100 grains, cob size variance analysis determined the statistical significance for the treatments; the best treatments for performance are those fertilization levels T3 (1L / 20l + EM) and T4 (1.5 L / 20l + EM) respectively, without the biol significantly influence these results and according to the analysis economical for the effect of biol more effective microorganisms (EM) on the agronomic performance of maize (Zea mays l.) is the best treatment T4 with RCB 2.1